Relationship between Leverage and Firm Size Toward to Real Earning Management (Unit Analysis of Mining Company Indonesia Exchange Stock Period 2012 Until 2015) - Barus, Irene Sukma Lestari; Sarumpaet, Tetty Lasniroha; Edison, Acep; Maisyarah, Renny; Pulungan, Edrida (Journal of Reviews on Global Economics, 2019)
This study found new results from the development of previous research. Previous research, earnings management is measured through discreationary accruals by disbursing total accruals with non-discreationary accruals using the Jones Modified model (Dechow et al., 1995) with the formula TA = Nit – CFOit. Previous research and this study were conducted on mining companies listed on the Indonesian stock exchange in the period 2012 to 2015. The results of previous studies that leverage had no effect on earnings management and earnings management is an intervening variable that has a significant influence on earnings quality. (Irene Barus et al., 2018). This study aims to analyze the relationship between leverage ratio and firm size to real earnings management using discretionary accruals through real daily earnings management activities. Managers tend to choose earnings management through real activity manipulation rather than earnings management through accruals (Graham et al. 2005; Roychowdhury (2006: 338). The results of this study indicate leverage variables have a positive and significant effect on real earnings management activities.